Intestinal short-chain fatty acids spatially regulate the antibiotic tolerance and virulence of avian pathogenic Escherichia coli - Chong Ling; Lulu Ren; Yaru Song; Qingyun Cao; Hui Ye; Zemin Dong; Changming Zhang; Dingyuan Feng; Jianjun Zuo; Weiwei Wang (Poultry Science)
Avian pathogenic Escherichia coli (APEC) represents a key pathogen severely threatening the poultry production, as well as food safety and public health. At present, the infection by APEC is hard to be prevented and controlled, because it possesses considerable virulence factors and high insensitivity to antibiotics. Short-chain fatty acids (SCFAs), the primary metabolites of intestinal probiotics, are considered to contribute to maintain intestinal health partially through inhibiting the activity of detrimental bacteria in gut. However, the effects of SCFAs on APEC activity and the underlying mechanisms remain unclear. In this study, we simulated the concentrations of SCFAs in the ileum (i-SCFA) and cecum (c-SCFA) of chickens to investigate their effects on the growth, virulence factor expression, and antibiotic tolerance of APEC. The results indicated that i-SCFA treatment activated the expression of APEC virulence genes, whereas c-SCFA treatment inhibited APEC growth, virulence gene expression, and ampicillin tolerance. Moreover, we observed different response mechanisms of APEC to SCFAs and the equal-pH inorganic acid (hydrochloric acid), which may be attributable to the partial dissociation property and membrane penetration characteristic of SCFAs. Additionally, SCFAs exhibited spatial (intestinal segment-specific) effects on the expression of extracellular and intracellular H+ sensing genes in APEC, with i-SCFA promoting and c-SCFA inhibiting their expression, particularly the intracellular pH homeostasis-regulating gene tnaA. It is known that tnaA encodes tryptophanase that catalyzes the conversion of tryptophan into indole, an important extracellular signaling molecule of bacteria. Further investigation revealed that the addition of indole reversed the inhibitory effects of c-SCFA on virulence gene expression and ampicillin tolerance of APEC. In summary, this study demonstrates that SCFAs spatially regulate APEC growth, virulence gene expression and antibiotic tolerance potentially by implicating in the disruption of intracellular pH homeostasis and interference with tryptophan metabolism.